Integration of Artificial Intelligence in the Preservation of Regional Arts and Languages: A Digital Humanities Approach in Indonesia - Malathy Batumalay; Haryono; Masrin (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
The development of artificial intelligence (AI) technology has opened up new opportunities for the preservation of cultural heritage, including endangered regional arts and languages. This study aims to analyze how the application of AI in the context of digital humanities can support efforts to document, revitalize, and disseminate local culture in Indonesia. The method used is descriptive-qualitative with a literature study approach and policy analysis of digital culture preservation projects that have been running, such as Google AI for Indigenous Languages and the Digital Culture program of the Ministry of Education, Culture, Research, and Technology. The results show that the integration of AI through Natural Language Processing (NLP), machine translation, speech recognition, and digital archiving is able to accelerate the process of documentation and learning of regional languages and encourage the participation of the creative community in the preservation of traditional arts. However, the main challenges lie in the limitations of linguistic data, algorithmic bias, and technological gaps between regions. This study concludes that the successful implementation of AI-based digital humanities depends on multidisciplinary collaboration between governments, academics, cultural communities, and technology developers.